The Childfree Discourse in Contemporary Islamic Family Law and Human Rights: Insights from Young Muslim Academics in Indonesia - Khoiruddin Nasution; Zezen Zainul Ali; Mufrod Teguh Mulyo; Syamruddin Nasution; Syaefullah (MILRev: Metro Islamic Law Review, 2026)
The childfree phenomenon has triggered critical debates in contemporary Islamic family law and human rights discourses. This study examines the primary narrative constructions of childfree individuals as understood by young academics at State Islamic Higher Education Institutions in Indonesia. This study uses a qualitative approach, employing interviews and focus group discussions with 17 doctoral students from diverse academic backgrounds. Two theoretical frameworks were used: Halverson's Main Narrative Theory was employed to identify primary and alternative narratives in the formation of social meaning related to the childfree phenomenon. Maqāṣid al-sharī‘ah, as the objectives of Islamic law, is used to examine the religious dimension in the formation of contemporary Islamic family law. The research results revealed three narrative configurations. First, the narrative of individual piety, which views children as a divine trust and part of the maqāṣid al-sharī‘ah, specifically ḥifẓ al-naṣl (protection of lineage), perceives childless households as contrary to natural values and the objectives of marriage. Second, the narrative of human rights emphasises bodily autonomy and reproductive freedom for couples in accordance with international principles. Third, the integrative narrative arises from reflective academics who strive to balance individual piety with the principle of public benefit through a contextual approach to tanzīm al-nasl (family planning). This study contributes to Islamic family law policy in Indonesia by promoting more inclusive regulatory formulations and serves as a foundation for religious institutions and policymakers to develop contextual policies addressing contemporary issues.